Den inderlige deltagelse - Baunvig, Katrine Frøkjær (Grundtvig-studier, 2014)
Den inderlige deltagelse Katrine Frøkjær Baunvig Devoted Participation Grundtvig’s liturgical focal point was congregants’ devoted participation in the joint singing of hymns during the Sunday Service. In his opinion the outcome of the song was manifold. He observed first that by arousing the congregation singing tightened emotional bonds. He also saw that the collective and physical experience was the foundation upon which the individual congregant prepared him- or herself emotionally for accepting the beliefs held within the historically saturated Christian semantic universe of the hymn texts. These observations constitute the backbone of the anti-aesthetic and pragmatic views on hymnal song that Grundtvig explicated in his academic writings in the 1820’s and onwards. He implicitely integrated these points into the hymns. In his emphasis on collective and “devoted participation,” he anticipates a subject that sociologist of religion and ritual scholar Émile Durkheim would half a century later scientifically and theoretically elaborate under the name “collective effervescence.”